Forming of competitive potential by higher educational institution - Inna Churnosova (Cхід)
Competitive potential of higher educational institutions is presented as quality-quantitative parameters of supply. For the calculation of parameters an index "the licensed enrolment" is utilized. Proofs of absence of co-ordination in operating of educational under forming of competition potential are adduced. The low level of maturity of competitive relations of educational establishments results in uncontrolled growth of aggregate supply. This circumstance presupposes of competitive activity intensification local market of services of higher education.